2001
DOI: 10.4049/jimmunol.166.6.4223
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Matrix-Degrading Phenotype in Human Tuberculosis In Vitro and In Vivo

Abstract: Tuberculous meningitis is characterized by cerebral tissue destruction. Monocytes, pivotal in immune responses to Mycobacterium tuberculosis, secrete matrix metalloproteinase-9 (MMP-9), which facilitates leukocyte migration across the blood-brain barrier, but may cause cerebral injury. In vitro, human monocytic (THP-1) cells infected by live, virulent M. tuberculosis secreted MMP-9 in a dose-dependent manner. At 24 h, MMP-9 concentrations increased 10-fold to 239 ± 75 ng/ml (p = 0.001 vs controls). MMP-9 mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 45 publications
8
116
0
Order By: Relevance
“…However, it does appear in a range of inflammatory diseases of the CNS where it is thought to contribute to damage of the parenchymal tissues and the BBB (10,34). In tuberculous meningitis patients, CSF MMP-9 concentrations are significantly associated with mortality and local tissue damage (12). Astrocytes did not secrete MMP-9 after direct infection with M. tuberculosis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, it does appear in a range of inflammatory diseases of the CNS where it is thought to contribute to damage of the parenchymal tissues and the BBB (10,34). In tuberculous meningitis patients, CSF MMP-9 concentrations are significantly associated with mortality and local tissue damage (12). Astrocytes did not secrete MMP-9 after direct infection with M. tuberculosis.…”
Section: Discussionmentioning
confidence: 94%
“…MMP-9 concentrations are increased in cerebrospinal fluid (CSF) from patients with CNS-TB (3,11) and we showed that MMP-9 concentrations are associated with neurological complications and death (12). The effect of active tuberculous on CSF TIMP-1 concentrations is variable and may be increased or remain unchanged (11,12).…”
Section: T Uberculosis Of the Cns (Cns-tb)mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathological response to Mycobacterium tuberculosis (Mtb) infection is characterised by extensive tissue breakdown including caseous necrosis, and later fibrosis. Tissue destruction in TB requires degradation of matrix proteins including collagen and elastin, and several studies have implicated matrix metalloproteinases (MMP) in pathogenesis [1][2][3]. MMP are a group of 23 related zinc-dependent enzymes that together are capable of degrading all components of the extracellular matrix (ECM) [4].…”
mentioning
confidence: 99%
“…Fibrillar collagens, which are highly resistant to enzymatic cleavage, are important constituents of the pulmonary extracellular matrix. However, collectively, MMPs are able to degrade all components of the extracellular matrix, resulting in cavities [4], and about a decade ago it was recognised that lung extracellular matrix destruction by MMPs was essential to tuberculosis [5]. The destruction of extracellular matrix by MMPs allows mycobacteria to spread from the interstitium to the airways, and results in cavities with an immunodeficient milieu in which mycobacteria can proliferate as a consequence of a missing protective immune response.…”
mentioning
confidence: 99%